Anti-inflammatory effects of hederagenin on diabetic cardiomyopathy via inhibiting NF-κB and Smads signaling pathways in a type-2 diabetic mice model. Issue 45 (21st August 2019) - Li, Ying; Dong, Junli; Shang, Yinghui; Zhao, Qiangqiang; Li, Pengcheng; Wu, Bin
Abstract : Hederagenin (HED) is a bioactive natural compound of pentacyclic triterpenes extracted from many medicinal plants. Abstract : Hederagenin (HED) is a bioactive natural compound of pentacyclic triterpenes extracted from many medicinal plants. It has a wide range of antitumor cytotoxic effects and significant anti-inflammation effects. However, at present, it is unclear whether HED can inhibit cardiac remodelling caused by diabetic cardiomyopathy. In this study, we evaluated the effects of HED on pathological abnormalities in cardiac structures and cardiac insufficiency caused by diabetic cardiomyopathy and focused on the inflammatory signalling pathways of the diabetic heart. Treatment with HED reduced pro-inflammatory cytokines, the heart and body mass of diabetic db/db mice but had no effect on fasting plasma glucose (FPG). Moreover, after HED treatment, the cardiac dysfunction of diabetic mice was relieved, and myocardial hypertrophy and fibrosis decreased. Furthermore, HED inhibited the nuclear translocation of nuclear factor-κB (NF-κB) and Smads and decreased the transcriptional activity of NF-κB and Smads. Additionally, the expression levels of transforming growth factor (TGF)-β1 and collagen I, which are target downstream molecules of the NF-κB and Smads signalling pathways, were also decreased in diabetic hearts. Taken together, our findings suggest that the cardioprotective effect of HED may be achieved by reducing the activation of inflammation-associated NF-κB and Smads signalling. We suggest that the protective effect of HED on the diabetic heart, as revealed in this study, should be further explored in-depth to elucidate its cell biology and molecular mechanisms.